Characteristics and Transformation of Pacific Winter Water on the Chukchi Sea Shelf in Late Spring - Pacini, Astrid; Moore, George William Kent; Pickart, Robert S.; Nobre, Carolina; Bahr, Frank; Våge, Kjetil; Arrigo, Kevin R. (Journal of Geophysical Research: Oceans, 2020)
Data from a late spring survey of the northeast Chukchi Sea are used to investigate various aspects of newly ventilated winter water (NVWW). More than 96% of the water sampled on the shelf was NVWW, the saltiest (densest) of which tended to be in the main flow pathways on the shelf. Nearly all of the hydrographic profiles on the shelf displayed a two‐layer structure, with a surface mixed layer and bottom boundary layer separated by a weak density interface (on the order of 0.02 kg/m3). Using a polynya model to drive a one‐dimensional mixing model, it was demonstrated that, on average, the profiles would become completely homogenized within 14–25 hr when subjected to the March and April heat fluxes. A subset of the profiles would become homogenized when subjected to the May heat fluxes. Since the study domain contained numerous leads within the pack ice—many of them refreezing—and since some of the measured profiles were vertically uniform in density, this suggests that NVWW is formed throughout the Chukchi shelf via convection within small openings in the ice. This is consistent with the result that the salinity signals of the NVWW along the central shelf pathway cannot be explained solely by advection from Bering Strait or via modification within large polynyas. The local convection would be expected to stir nutrients into the water column from the sediments, which explains the high nitrate concentrations observed throughout the shelf. This provides a favorable initial condition for phytoplankton growth on the Chukchi shelf. publishedVersion